Prevalence of RTI/STI symptoms among adolescent girls in an urban slum of Sambalpur - Padmavati Majhi¹, Renu Sulakhe , Smita Kumari Panda (Perspectives In Medical Research, 2014)
Introduction: Adolescents form a major part of our population and about half of this population is made up of females. Their reproductive and sexual behavior in this period have far reaching consequences on their health as they develop into adulthood. But not many studies have been done in India to find out the prevalence of RTIs and STIs in this particular group. Materials and Methods: A cross-sectional study was conducted among the adolescent girls in the age group of 10-19 years in the urban slums of Sambalpur from January 2009 to June 2010. The data was collected by personal interview using a predesigned and pre-tested questionnaire. Atotal of 404 girls were interviewed in the study. Results: The overall prevalence of RTI and STI symptoms in the adolescent girls was found to be INTRODUCTION The World Health Organization refers to those aged 10-19 years as adolescents. Adolescent period has again been divided into three groups: Early adolescence (10-13 years), mid adolescence (13-15 years) and late adolescence (15-19 years). Adolescents in India constitute 21.8% of the total population (Census 2001) and about half of this population is made up of females. ¹ Adolescents encompass a significant proportion of reproductive age group and are playing a important role in determining the future size and growth pattern of the Perspectives in Medical Research | September - December 2014 | Vol 2 | Issue 3 22.5% and the most common symptom was vaginal discharge. A total of 69 girls in the 15-19 years age group were having symptoms of RTI/STI whereas 45 girls were educated up to primary and 63 girls belonging to class V socioeconomic status. A statistically highly significant difference was observed in the context of age, literacy, socioeconomic status and the symptoms of RTI/STI ( p<0.001). Conclusion: A significant proportion of adolescent girls were affected by RTI/STI as every fifth girl reported positive symptoms. Age of the girl, literacy and socioeconomic status were found to be significantly associated with the symptoms of RTI/STI. There is an urgent need to address the issue and provide reproductive health interventions in underprivileged areas in urban localities.